(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article analyzes the historical development of the electoral system in the sovereign Kyrgyz Republic and the reforms implemented within it. The author examines the constitutional and legal foundations of the electoral system and compares the features of various electoral models — majoritarian, proportional, and proportional-preferential systems. Key changes in the electoral process are reviewed in stages, beginning in 1991. Special attention is given to the political events of 2005, 2010, and 2020, emphasizing their connection to the transformation of the electoral system. The article also explores the legislative innovations introduced following the 2021 referendum, including the combination of single-member district voting and partylist voting, analyzing the advantages and disadvantages of this hybrid model. Particular focus is placed on ensuring public trust in elections and the need for legal clarity and consistency in electoral procedures.